Social Determinant Factors as Dengue Hemorrhagic Fever Prevention in Banjar Pedungan, South Denpasar - Anny Eka Pratiwi; Made Indra Wijaya (International Journal of Health and Social Behavior, 2026)
Dengue Hemorrhagic Fever (DHF) remains an endemic health problem in Denpasar, with incidence rates increasing over the past five years, reaching 43.97 (2021), 109.87 (2022), 184.23 (2023), 126.01 (2024), and 169.32 per 100,000 population (2025). Cadres play an important role in the success of DHF prevention programs by facilitating information delivery, periodic monitoring, and community participation in preventive actions. This study aimed to evaluate community knowledge, attitudes, and practices regarding DHF prevention in Banjar Pedungan, South Denpasar. A mixed-methods approach was employed using purposive sampling involving 74 householders in South Denpasar. The findings showed that 66.7% of families had good knowledge and attitudes, 61.9% had good knowledge and practices, and 76.3% had good attitudes and practices related to DHF prevention. Fogging implementation was adjusted based on regional evaluations of increasing DHF cases. These findings indicate that community knowledge, attitudes, and practices toward DHF prevention were generally good. The study recommends strengthening DHF prevention through effective social media programs, adequate funding, regular monitoring and evaluation, and increased human resources to optimize prevention efforts.